Circulating exo-miR-154-5p regulates vascular dementia through endothelial progenitor cell-mediated angiogenesis - Han, Xue; Zhou, Li; Tu, Yu; Wei, Jiajia; Zhang, Jiajia; Jiang, Guojun; Shi, Qiaojuan; Ying, Huazhong (Frontiers in Cellular Neuroscience, 2022)
Background: Vascular dementia (VaD) mainly results from cerebral vascular lesions and tissue changes, which contribute to neurodegenerative processes. Effective therapeutic approaches to targeting angiogenesis may reduce mortality of VaD. Endothelial progenitor cells (EPCs) play a key role in postnatal angiogenesis. Many exosomal microRNAs (exo-miRNAs) have been reported to involve in the development of dementia. The present study was designed to investigate whether the expression profile of the exo-miRNAs is significantly altered in patient with VaD, and to reveal the function of differentially expressed miRNAs and the relevant mechanisms in EPC-mediated angiogenesis in VaD rat model. Results: Exosomes isolated from serum of VaD patients (n=7) and age-matched control subjects (n=7), and miRNA sequencing and bioinformatics analysis found that circulating exosome miRNA-155-5p, miRNA-154-5p, miR-132-5p and miR-1294 were upregulated in VaD patients. The expression of miRNA-154-5p was further verified to be upregulated in of clinical samples (n=23) and 2-vessel occlusion-induced VaD rat model by RT-qPCR. Notably, miRNA-154-5p inhibition in bone marrow-EPCs (BM-EPCs) from VaD rats improved EPC functions including tube formation, migration and adhesion, and elevated concentrations of vascular endothelial growth factor (VEGF) and stromal cell derived factor-1α (SDF-1α). The mRNA levels of ICAM-1, VCAM-1, and MCP-1 were reduced in miRNA-154-5p inhibited EPCs. In addition, miRNA-154-5p inhibition increased the level of superoxide dismutase (SOD), and decreased reactive oxygen species (ROS) in EPCs. PRKAA2 was choose as a promising target gene of miR-154-5p, and miRNA-154-5p inhibition upregulated the protein expression of AMPKα2. Furthermore, upregulation of miR-154-5p markedly diminished EPC functions, and inhibited angiogenesis following EPC transplantation in VaD Rats. Conclusions: Circulating exo-miR-154-5p was upregulated in VaD patients, and miR-154-5p upregulation was associated with impaired EPC functions and angiogenesis in VaD rat model. Therefore, miR-154-5p is a promising biomarker and therapeutic strategy for vascular dementia.